Right ventricular dysfunction in patients with acute respiratory distress syndrome receiving venovenous extracorporeal membrane oxygenation - Brown, Tyler N.; Brogan, Thomas V. (Frontiers in Cardiovascular Medicine, 2023)
Acute respiratory distress syndrome is characterized by non-cardiogenic pulmonary edema, decreased pulmonary compliance, and abnormalities in gas exchange, especially hypoxemia. Patients with acute respiratory distress syndrome (ARDS) who receive support with venovenous (V-V) extracorporeal membrane oxygenation (ECMO) usually have severe lung disease. Many patients with ARDS have associated pulmonary vascular injury which can result in elevated pulmonary vascular resistance and right heart dysfunction. Since V-V ECMO relies upon preserved cardiac function, right heart failure has important implications for patient evaluation, management, and outcomes. Worsening right heart function complicates ARDS and disease processes. Given the increasing use of ECMO to support patients with ARDS, an understanding of right ventricular-ECMO and cardiopulmonary interactions is essential for the clinician. A narrative review of the manifestations of right heart dysfunction, as well as diagnosis and management strategies for the patient with ARDS on ECMO, is provided.